INITIAL GROWTH OF EUCALYPTUS CLONES IN THE FUNCTION OF NPK FERTILIZATION - Silva, H.A.S.; Buzetti, S.; Gazola, R.N.; Marques, G.G.; Teixeira Filho, M.C.M.; Gazola, R.P.D. (Revista Brasileira de Engenharia de Biossistemas, 2019)
NPK fertilization and the choice of genetic material are fundamental in the establishment and productivity of the crop. The objective of this study was to evaluate the effect of planting mineral fertilization on the growth of eucalyptus urophylla clones (Eucalyptus urophylla x Eucalyptus grandis) on Cerrado soil. The experiment was conducted from October 2015 to July 2017, at Campo Verde IV farm, located in the municipality of Selvíria - MS. The experimental design was a randomized complete block with 12 treatments and four replications, in a 3x4 factorial scheme, with three clones (I144, H13 and 1528) and four doses: 0, 160, 320 and 640 kg ha-1 of the formula 08-32-16 + 0.5% B, 0.5% Cu and 0.5% Zn. Each plot was composed of 42 plants, distributed in seven rows of six plants each, totaling 378.0 m2 of area, being considered useful area only the six central plants, totaling 54.0 m2. The diameter at breast height (DBH) and volume of wood with bark were evaluated at 17 months of age. Fertilization increased DBH and wood productivity for the three clones, with the 1528 being more productive.